Internet Use and Depressive Symptoms Among Older Adults in China - Yang, Hua-lei; Zhang, Shuo; Zhang, Si-qing; Xie, Lin; Wu, Yuan-yang; Yao, Yi-dan; Tang, Li-li; Li, Zhi-yun (Frontiers in Psychiatry, 2021)
This study investigated the effect of using the Internet on mental health in a sample of older Chinese people and the differences in mental health effects between subgroups with an analytical sample (n = 7,801) of adults aged over 60 years was drawn from the 2018 China Family Panel Studies. Mental health was evaluated using the CESD-8 Scale, and empirical analyses were performed. Older adults who used the Internet reported significantly lower depression scores. Subgroup analyses showed heterogeneity in the mental health effects of Internet use among different groups: older adults aged 60–70, women, rural residents, persons with lower education, and illiterate people were more sensitive to Internet use and experienced lower depression scores. Internet use and mental health were positively related among Chinese older adults. Policies should be designed to ensure that no one is being forgotten in the digital age—to ensure easy Internet access for older people.